2020
DOI: 10.1371/journal.pone.0239727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incidental physical activity on morphosyntactic processing in aging

Abstract: Older adults have difficulties in sentence comprehension when working memory (WM) load increases (e.g., multiple embedded clauses). Structured physical activity has been related to improvements in cognition; however, incidental physical activity (PA, i.e., unstructured daily physical activities), particularly incidental vigorous activity has been poorly studied in relation to its effects on behavior. Furthermore, no positive effect on language has been reported in either form of physical activity. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
1
0
4
Order By: Relevance
“…Studies involving the P3 component, the major focus of studies of event-related potentials, showed that exercise increases the amplitude of P3, possibly suggesting that exercise enhances the allocation of neural resources as part of a compensatory mechanism ( Chang et al, 2015 ). However, the results are controversial ( Gajewski and Falkenstein, 2018 ; Alatorre-Cruz et al, 2020 ).…”
Section: Functional Mechanismsmentioning
confidence: 99%
“…Studies involving the P3 component, the major focus of studies of event-related potentials, showed that exercise increases the amplitude of P3, possibly suggesting that exercise enhances the allocation of neural resources as part of a compensatory mechanism ( Chang et al, 2015 ). However, the results are controversial ( Gajewski and Falkenstein, 2018 ; Alatorre-Cruz et al, 2020 ).…”
Section: Functional Mechanismsmentioning
confidence: 99%
“…Stwierdzono również, że osoby starsze o wysokim poziomie aktywności fizycznej (pomiar za pomocą kwestionariusza) osiągają wyższą dokładność w zadaniach mierzących funkcjonowanie pamięci roboczej niż osoby starsze o niskim poziomie aktywności fizycznej w warunkach niskiego obciążenia pamięci roboczej, natomiast nie w warunkach wysokiego jej obciążenia. Zaobserwowano także różnice między grupami w odpowiedzi elektrofizjologicznej mózgu [57].…”
Section: Wyniki Przegląduunclassified
“…W omawianych badaniach podejmowana aktywność fizyczna była powiązana z wyższą wydajnością poznawczą i uwagą [37,54,55], jawną pamięcią relacyjną [38], wysokimi wynikami w miarach pamięci [36], poprawą funkcjonowania przestrzennej pamięci roboczej [39,47], poprawą pamięci przestrzennej [40,45,58] i bezpośredniej [41], a także funkcji wykonawczych [38,39,53,55,56,58], w tym pamięci roboczej [49,57].…”
Section: Wnioskiunclassified
See 2 more Smart Citations